(untitled) (Bangladesh Journal of Zoology, 2010)
The present study was conducted to assess the hatching success, survival and growth performances of Artemia franciscana cyst under three feeding regime with natural and artificial salt water. For the growth and development of Artemia three types of feed, namely Spirulina, Chlorella and commercial micro diet were used. Four types of natural and artificial salt waters were used. These were sea water, salt water natural salt solution, analytical salt solution and iodized salt solution. Comparing natural sea water with artificial salt water for the first 24 hours of the experimentation, the highest percentage of hatching was observed in natural sea water (78%) followed by iodized salt solution (43%), natural salt solution (25%) and analytical salt solution (25%). The maximum success of hatching commenced within 18 to 30 hours in all studied media. Beyond this time frame, the cysts which were not hatched out within 70 hours never showed success in hatching. The development of A. franciscana was found to be completed with high survival rate in the sea water with Spirulina feed. The natural sea water along with Spirulina feed at 28º-29ºC temperature and 7.5- 8.0 pH supported the highest hatching rate, survival and growth of A. franciscana larvae. Bangladesh J. Zool. 38(1): 1-6, 2010